Layered / rod-like eutectic high-entropy alloy and design method and preparation method thereof

By establishing a database and screening the eutectic alloy system, key alloy elements and doped alloy elements are determined, and a eutectic high-entropy alloy system is formed, which solves the problem that eutectic high-entropy alloys is difficult to accurately obtain eutectic structures, and achieves efficient eutectic Alloy design and preparation improves the strength and plasticity of the alloy.

CN119464880AActive Publication Date: 2025-02-18XIAN TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411511308.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

When designing and preparing eutectic high entropy alloys, it is difficult to accurately obtain complete eutectic structure, and it is difficult to quickly determine the interval in which the alloy system forms eutectics.

Method used

By establishing a database, obtaining the alloy composition and eutectic structure of the eutectic alloy system in the disclosed literature data, selecting eutectic alloy systems with layered sheet eutectic and/or rod eutectics to determine key alloy elements and doped alloys Elements form eutectic high entropy alloy system composed of at least five alloy elements.

Benefits of technology

It is realized quickly to determine the interval for forming eutectics in the alloy system, and to directly obtain non-equimolar ratio near/full eutectic high-entropy alloy components with structures of layered sheet eutectics and/or rod eutectics, thereby improving high entropy alloys The strength and plasticity make it have high strength and high toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464880A_ABST
    Figure CN119464880A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal materials and preparation thereof, and discloses a layered / rod-like eutectic high-entropy alloy and a design method and a preparation method thereof. The preparation method comprises the steps that alloy components and eutectic structure forms of an eutectic alloy system are obtained, and a database is established; a eutectic alloy system candidate set with lamellar eutectic and / or rod-like eutectic is screened, eutectic point components are obtained, and key alloy elements are determined; determining a doped alloy element candidate set to partially replace the key alloy elements, forming an eutectic high-entropy alloy system according to a predefined atom molar ratio content, and screening to obtain a alloy system meeting 6.5 lt; vEClt, VEClt; 8.38,-18 lt, 8.38,-18 lt; [delta] Hmix; and the melting point difference of the layered / rod-like eutectic high-entropy alloy meets the requirement that the temperature is less than or equal to 35 DEG C. The design method is easy and convenient to operate, complex calculation or formula deduction is not needed, secondary design is not needed, the eutectic forming interval of the alloy system can be rapidly determined, efficiency is high, and the success probability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials and preparation thereof, and in particular to a layer / rod-shaped eutectic high entropy alloy and a design method and a preparation method thereof. Background Art

[0002] Eutectic high entropy alloy is a new type of alloy with great advantages. It has the advantages of both high entropy alloys and eutectic alloys, has high phase stability, overcomes the composition segregation phenomenon of high entropy alloys, and has good fluidity and castability. It reconciles the contradiction between strength and plasticity of metal materials and greatly improves the application prospects of high entropy alloys. Therefore, it has attracted strong attention from many researchers at home and abroad.

[0003] However, due to the multi-principal characteristics of high-entropy alloys, it is difficult to accurately obtain a complete eutectic structure when designing and preparing eutectic high-entropy alloys. Although there are many design methods for eutectic high-entropy alloys, such as the mixing enthalpy method, the simple mixing method, the infinite solid solution method, and the machine learning method, these methods either require the determination of the existing eutectic high-entropy alloy composition and secondary design based on this, or require simulation calculations through thermodynamic databases, which makes it difficult to quickly determine the range in which the eutectic can be formed for the selected alloy system of any component. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a layer / rod eutectic high entropy alloy and a design method and a preparation method thereof.

[0005] The layer / rod-shaped eutectic high entropy alloy and the design method and preparation method thereof of the present invention are realized by the following technical scheme:

[0006] The present invention provides a design method for a layer / rod-shaped eutectic high entropy alloy, comprising the following steps:

[0007] Step 1, create a database:

[0008] The alloy composition and eutectic microstructure of the eutectic alloy system are obtained from the public literature data, and the corresponding data of the eutectic microstructure is used as input data and the alloy composition of the eutectic alloy system is used as the corresponding output data to establish a database.

[0009] It should be noted that the present invention takes into account that structure determines performance, and different organizational morphologies have a great influence on the performance of the alloy. Generally speaking, eutectic alloys have three regular organizational morphologies: spherical eutectics, rod-shaped eutectics and lamellar eutectics. Among them, the spherical eutectic structure usually has higher toughness and impact resistance, but its strength and stiffness are lower; the lamellar eutectic structure usually has higher thermal stability and corrosion resistance, but its strength and stiffness are lower; the rod-shaped eutectic structure usually has higher strength and toughness, and the rod-shaped eutectic structure is equivalent to the reinforcement phase distributed in the metal solid solution matrix in a fibrous form. When bearing load, the fibrous reinforcement phase plays a major role. Therefore, under the same composition and grain size, the rod-shaped structure has good plasticity, toughness and fatigue resistance. Therefore, based on the above, the present invention attempts to achieve simultaneous improvement of the strength and plasticity of the high entropy alloy by designing an alloy component with the organizational morphology of lamellar eutectics and / or rod-shaped eutectics, so as to obtain a eutectic high entropy alloy with high strength and toughness.

[0010] In order to facilitate the screening of eutectic alloy systems with lamellar eutectics and / or rod-shaped eutectics according to the eutectic microstructure morphology in the eutectic alloy system, the present invention first establishes a database based on the alloy composition and eutectic microstructure morphology of the eutectic alloy system in the public literature data, that is, using the corresponding data of the eutectic microstructure morphology as input data and the alloy composition of the eutectic alloy system as the corresponding output data.

[0011] The alloy composition includes a eutectic point composition, and the eutectic point composition includes the type of alloy element at the eutectic point and the corresponding content of the type of alloy element.

[0012] Step 2: Determine the candidate set of basic alloying elements:

[0013] The database is screened with the organizational morphology including lamellar eutectics and / or rod-shaped eutectics as a constraint condition to obtain a candidate set of eutectic alloy systems having lamellar eutectics and / or rod-shaped eutectics; and the eutectic point composition of each eutectic alloy system in the candidate set of eutectic alloy systems is obtained as a candidate set of basic alloy elements.

[0014] It should be noted that the present invention uses the eutectic organizational morphology as input and the organizational morphology of lamellar eutectic and / or rod-shaped eutectic as a constraint condition to screen the database, thereby obtaining the eutectic alloy system data having the desired eutectic organizational morphology, wherein the obtained eutectic alloy system data having the desired eutectic organizational morphology includes the types of alloy elements of the eutectic point composition and the corresponding contents of the alloy element types.

[0015] The present invention obtains the eutectic point composition of each eutectic alloy system in the eutectic alloy system candidate set, that is, obtains the alloy composition that can form lamellar eutectics and / or rod-shaped eutectics, and uses the alloy composition as the basic alloy element candidate set to ensure that the obtained alloy composition can form lamellar eutectics and / or rod-shaped eutectics.

[0016] Step 3, determine the key alloying elements:

[0017] The types and contents of the alloying elements of the eutectic point composition in the basic alloying element candidate set are obtained, the types of the alloying elements of the eutectic point composition are sorted in order according to the content, and the type of alloying element with the largest content is taken as the key alloying element.

[0018] It should be noted that the present invention first determines the key alloying elements so that the key alloying elements can be used as a basis for subsequent improvement of the strength and plasticity of the alloy by introducing doping alloying elements that can be alloyed with the key alloying elements.

[0019] The present invention takes into account the factors affecting the organization and mechanical properties of high entropy alloys by multi-principal elements, and uses the alloy element with the largest content in the eutectic point composition as the key alloy element to achieve the effect of refining the eutectic organization and enhancing the overall strength and plasticity.

[0020] Step 4: Determine the candidate set of doping alloy elements:

[0021] The database is screened using the types of alloy elements that can form an infinite solid solution and / or have a eutectic tendency with the key alloy element as constraint conditions to obtain a candidate set of doping alloy elements.

[0022] It should be noted that in order to ensure that the added doping alloy elements can improve the strength and plasticity of the key alloy elements after introduction, the present invention uses alloy elements that can infinitely dissolve or exist in eutectic with the key alloy elements as constraints.

[0023] In some preferred embodiments of the present invention, the alloy elements in the database are screened based on the constraints that the atomic radius is close to that of the key alloy element, the crystal structure is the same, and there is only a single-phase region below the liquidus line in the binary phase diagram formed with the key alloy element, and the alloy elements obtained by the screening are the alloy elements that can be infinitely dissolved with the key alloy element.

[0024] In some preferred embodiments of the present invention, the alloy elements in the database are screened with the valence electron concentration VEC≥8 of the alloy formed with the key alloy element as a constraint condition, and the alloy elements screened are the alloy elements that have a eutectic tendency with the key alloy element.

[0025] Step 5, establish a candidate set of lamellar / rod eutectic high-entropy alloys:

[0026] Taking several doped alloy elements selected from the candidate set of doped alloy elements as doping sources, partially replace the key alloy elements in the candidate set of base alloy elements, and form a eutectic high-entropy alloy system composed of at least five alloy elements according to the predefined atomic molar ratio content, so as to establish a candidate set of lamellar / rod eutectic high-entropy alloys.

[0027] It should be noted that when partially replacing the key alloy elements in the candidate set of base alloy elements, the number of selected doped alloy elements is related to the actually determined base alloy elements. When the eutectic point composition in the candidate set of base alloy elements is a ternary system alloy, at least 2 doped alloy elements are selected from the candidate set of doped alloy elements. When the eutectic point composition in the candidate set of base alloy elements is a binary system alloy, at least 3 doped alloy elements are selected from the candidate set of doped alloy elements.

[0028] In some preferred embodiments of the present invention, when the screened eutectic point composition is a ternary eutectic point composition composed of three alloy elements A, B, and C, a eutectic high-entropy alloy system composed of six alloy elements is formed according to the predefined atomic molar ratio content, and the eutectic high-entropy alloy system meets the following requirements:

[0029] Its chemical composition expression is A a B b C c D d E e F f ; where A is the key alloy element, a is the atomic molar ratio content of element A, 30% ≤ a% ≤ 54%; B and C are the two alloy elements other than the key alloy element in the eutectic point composition, b is the atomic molar ratio content of element B, 0% < b% ≤ x, and x is the atomic molar ratio content of element B in the eutectic point composition; c is the atomic molar ratio content of element C, 0% < c% ≤ y + 1, and y is the atomic molar ratio content of element C in the eutectic point composition; D and E are alloy elements that can be infinitely solid-solved with the key alloy element, d is the atomic molar ratio content of element D, 0% < d% ≤ 15%; e is the atomic molar ratio content of element E, 0% < e% ≤ 30%; F is an alloy element with a eutectic tendency with the key alloy element, f is the atomic molar ratio content of element F, 0% < f% ≤ 30%; and a + b + c + d + e + f = 100.

[0030] Step 6, preliminary screening:

[0031] Taking the valence electron concentration VEC satisfying 6.5 < VEC < 8.38 and the mixing enthalpy satisfying -18 < ΔHmix < -6 as constraints, screen the candidate set of the layer / rod eutectic high-entropy alloy to obtain the candidate layer / rod eutectic high-entropy alloy.

[0032] Step 7, final screening:

[0033] Determine the phase compositions of the eutectic two phases of the candidate layer / rod eutectic high-entropy alloy. Taking the melting point difference between the phase compositions of the eutectic two phases ≤ 35 °C as a constraint, screen the candidate layer / rod eutectic high-entropy alloy, and then the layer / rod eutectic high-entropy alloy is obtained.

[0034] In some preferred embodiments of the present invention, the melting point difference between the eutectic two phases is obtained through the following steps:

[0035] Calculate the melting point difference corresponding to the phase compositions of the eutectic two phases through the JMatPro solidification simulation phase diagram.

[0036] In some preferred embodiments of the present invention, the phase compositions of the eutectic two phases of the candidate layer / rod eutectic high-entropy alloy are determined through the following steps:

[0037] Simulate the X-ray diffraction spectrum of the candidate layer / rod eutectic high-entropy alloy through Jade software, and analyze the obtained X-ray diffraction spectrum to determine the phase compositions of the two phases.

[0038] The present invention also provides a layer / rod eutectic high-entropy alloy designed based on the above design method. The layer / rod eutectic high-entropy alloy is based on the ternary eutectic point composition composed of three alloy elements A, B, and C as the matrix, and is obtained by introducing doping alloy elements D, E, and F. And the chemical composition expression of the layer / rod eutectic high-entropy alloy is A a B b C c D d E e F f ; wherein, A is the key alloy element, a is the atomic molar ratio content of element A, 30% ≤ a% ≤ 54%; b is the atomic molar ratio content of element B, 0% < b% ≤ x, and x is the atomic molar ratio content of element B in the eutectic point composition; c is the atomic molar ratio content of element C, 0% < c% ≤ y + 1, and y is the atomic molar ratio content of element C in the eutectic point composition; D and E are alloy elements that can be infinitely solid-solved with the key alloy element, d is the atomic molar ratio content of element D, 0% < d% ≤ 15%; e is the atomic molar ratio content of element E, 0% < e% ≤ 30%; F is an alloy element having a eutectic tendency with the key alloy element, f is the atomic molar ratio content of element F, 0% < f% ≤ 30%; and a + b + c + d + e + f = 100.

[0039] In some preferred embodiments of the present invention, the layer / rod-shaped eutectic high entropy alloy has a two-phase structure consisting of a first phase and a second phase; wherein the first phase is a BCC phase or a FCC phase; and the second phase is a Laves phase.

[0040] In some preferred embodiments of the present invention, the layer / rod eutectic high entropy alloy is an iron-based eutectic high entropy alloy, and its chemical composition expression is Fe a Al b Ta c Co d Cr e Ni f ; Wherein, a is the atomic molar content of Fe element, 30%≤a%≤54%; b is the atomic molar content of Al element, 3%≤b%≤8%; c is the atomic molar content of Ta element, 5%≤c%≤8%; d is the atomic molar content of Co element, 5%≤d%≤15%; e is the atomic molar content of Cr element, 20%≤e%≤30%; f is the atomic molar content of Ni element, 5%≤f%≤30%; and a+b+c+d+e+f=100. In some more preferred embodiments of the present invention, the layer / rod eutectic high entropy alloy has a eutectic alloy microstructure of BCC phase + Laves phase, wherein the BCC phase is Fe2AlCr phase, and the Laves phase is hexagonal close-packed Fe2Ta. In some other preferred embodiments of the present invention, the layer / rod-shaped eutectic high entropy alloy has a eutectic alloy microstructure of FCC+Laves phase, wherein the FCC phase is Fe3Ni phase and the Laves phase is close-packed hexagonal Fe2Ta.

[0041] The present invention also provides a method for preparing the above-mentioned layer / rod-shaped eutectic high entropy alloy, comprising the following steps:

[0042] S1. According to the stoichiometric relationship of the chemical composition of the layered / rod-shaped eutectic high entropy alloy designed in the present invention, weigh the corresponding masses of various preparation raw materials for later use.

[0043] S2, the weighed raw materials are placed in a non-consumable arc melting water-cooled copper crucible in order from low to high melting points.

[0044] S3, after vacuum treatment, protective gas is filled in, and after deoxygenation treatment, non-consumable arc melting treatment is performed to obtain a molten liquid.

[0045] S4, after casting the molten liquid, the layer / rod-shaped eutectic high entropy alloy is obtained.

[0046] In some preferred embodiments of the present invention, the non-consumable arc melting process is performed at least 5 times; and during each process, the current is controlled at 600A to 650A, and the duration is 3min to 5min.

[0047] In some preferred embodiments of the present invention, the protective gas is argon with a purity of ≥99.999wt.%.

[0048] In some preferred embodiments of the present invention, the vacuum treatment is performed to a vacuum degree of ≤1×10 -3 Pa.

[0049] In some preferred embodiments of the present invention, the deoxygenation treatment is performed by placing the titanium sponge and various preparation raw materials in a non-consumable arc melting water-cooled copper crucible, and then melting the titanium sponge for 2 minutes to 3 minutes to remove residual oxygen in the furnace.

[0050] In some preferred embodiments of the present invention, the purity of each preparation raw material is ≥99.95%; each preparation raw material is in block or granular form.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] The present invention establishes a database based on the alloy composition and eutectic structure morphology of the eutectic alloy system in the public literature data, that is, using the corresponding data of the eutectic structure morphology as input data and the alloy composition of the eutectic alloy system as the corresponding output data, so that the database can be screened with the eutectic structure morphology in the actual required eutectic alloy system as input and the structure morphology as lamellar eutectic and / or rod-shaped eutectic as constraint conditions, and then the eutectic alloy system data with lamellar eutectic and / or rod-shaped eutectic is screened. Then, by obtaining the eutectic point composition of each eutectic alloy system in the candidate set of the eutectic alloy system, the alloy composition that can form lamellar eutectic and / or rod-shaped eutectic is obtained, and the alloy composition is used as the basic alloy element candidate set to ensure that the obtained alloy composition can form lamellar eutectic and / or rod-shaped eutectic. The present invention uses the alloy element with the largest content in the eutectic point composition as the key alloy element to achieve the refinement of the eutectic structure and the enhancement of overall strength and plasticity. Then, the database is screened with the types of alloying elements that can be infinitely solid-dissolved and / or have a eutectic tendency with the key alloying element as constraints to obtain a candidate set of doped alloying elements. Several doped alloying elements selected from the candidate set of doped alloying elements are used as doping sources to partially replace the key alloying elements in the candidate set of basic alloying elements, and a eutectic high entropy alloy system composed of at least five alloying elements is formed according to a predefined atomic molar ratio content to ensure that the added doped alloying elements can improve the strength and plasticity of the key alloying elements after introduction. Finally, the valence electron concentration and mixing enthalpy are used as criteria, and the melting point difference between the two phases of the eutectic is used as an auxiliary criterion to ensure that the chemical composition of the obtained layer / rod eutectic high entropy alloy can be prepared by smelting to form the corresponding layer / rod eutectic high entropy alloy sheet.

[0053] The present invention is easy to operate, does not require complicated calculations or formula deductions, and does not require secondary design. The present invention can quickly determine the interval in which the alloy system forms a eutectic, and directly obtain a non-equimolar ratio near / full eutectic high-entropy alloy component with a lamellar eutectic and / or a rod-shaped eutectic structure. The design of the present invention can simultaneously improve the strength and plasticity of the high-entropy alloy, so that the designed non-equimolar ratio near / full eutectic high-entropy alloy component has high-strength and high-toughness properties.

[0054] The design method of the present invention is established on the basis of the experimental results reported in previous literature, has a theoretical basis, can obtain multiple high-entropy amorphous alloy components at one time, realizes the extensive design of eutectic high-entropy alloys, has high design efficiency and high success probability, and reduces the trial and error workload. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 is the Fe of Example 1 50 Al8Ta7Co5Cr 25Scanning electron microscope image of Ni5.

[0056] Figure 2 is the Fe of Example 1 50 Al8Ta7Co5Cr 25 Bright field image of Ni5 obtained by transmission scanning electron microscopy.

[0057] Figure 3 is the Fe of Example 1 50 Al8Ta7Co5Cr 25 X-ray diffraction spectrum of Ni5.

[0058] Figure 4 is the Fe of Example 1 50 Al8Ta7Co5Cr 25 The temperature rise endothermic curve of Ni5 measured by differential scanning calorimetry.

[0059] Figure 5 is the Fe of Example 1 50 Al8Ta7Co5Cr 25 Compressive stress-strain curve of Ni5.

[0060] Figure 6 The Fe of Example 2 45 Al8Ta7Co 10 Cr 20 Ni 10 Scanning electron microscope image of .

[0061] Figure 7 Fe of Comparative Example 1 55 Al8Ta7Co5Cr 20 Scanning electron microscope image of Ni5.

[0062] Figure 8 is Fe of Example 3 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 Scanning electron microscope image of .

[0063] Fig. 9 is Fe of Example 3 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 X-ray diffraction spectrum of .

[0064] Fig.10 The Fe of Example 4 36 Al7Ta9Co 10 Cr 19Ni 19 Scanning electron microscope image of .

[0065] Fig.11 Fe of Comparative Example 2 36 Al7Ta9Co 10 Cr 19 Ni 19 Scanning electron microscope image of .

[0066] Fig.12 Fe of Comparative Example 2 36 Al7Ta9Co 10 Cr 19 Ni 19 X-ray diffraction spectrum of . DETAILED DESCRIPTION

[0067] The present invention will take the iron-based eutectic high entropy alloy as an example, and the technical solutions in the embodiments of the invention will be clearly and completely described through the following embodiments in combination with the drawings of the specification.

[0068] The present invention provides a design method for a layer / rod-shaped eutectic high entropy alloy, comprising the following steps:

[0069] Step 1, create a database:

[0070] The alloy composition and eutectic microstructure of the eutectic alloy system in the public literature data are obtained to establish a database, wherein the alloy composition includes the eutectic point composition, and the eutectic point composition includes the type of alloy element at the eutectic point and the corresponding content of the alloy element type.

[0071] Step 2: Determine the candidate set of basic alloying elements:

[0072] 2.1) Taking the organizational morphology including lamellar eutectics and / or rod-shaped eutectics at the same time as a constraint condition, the database is screened to obtain a candidate set of eutectic alloy systems having both lamellar eutectics and rod-shaped eutectics.

[0073] 2.3) Obtain the eutectic point composition of each eutectic alloy system in the eutectic alloy system candidate set. Since Fe-Al-Ta has a ternary eutectic and the eutectic point is Fe 85 Al8Ta7, therefore Fe 85 Al8Ta7 is selected as a candidate set of basic alloying elements.

[0074] Step 3, determine the key alloying elements:

[0075] Get Fe 85The types and contents of alloying elements in Al8Ta7 are sorted in descending order of content as follows: Fe 85%, Al 8%, Ta 7%. That is, the key alloying element is Fe, the alloying element with the highest content.

[0076] Step 4, determine the doping alloying elements:

[0077] Since Cr elements can be infinitely solid-solved with Fe, Co is chemically similar to Fe and Cr, and the addition of Co can reduce the melting point difference between the two phases, so Co and Cr are alloying elements that can be infinitely solid-solved with the key alloying element; Ni has a eutectic tendency with Fe, so Co, Cr, and Ni elements are used together as doping alloying elements.

[0078] Step 5, establish a candidate set of layer / rod eutectic high-entropy alloys:

[0079] Using Co, Cr, and Ni elements together as the doping source, partially replace Fe in 85 Fe in Al8Ta7. The chemical composition expression of the predefined layer / rod eutectic high-entropy alloy is Fe a Al b Ta c Co d Cr e Ni f ; where a is the atomic molar ratio content of Fe element, 30% ≤ a% ≤ 54%; b is the atomic molar ratio content of Al element, 0% < b% ≤ 8%; c is the atomic molar ratio content of Ta element, 0% < c% ≤ 8%; d is the atomic molar ratio content of Co element, 0% < d% ≤ 15%; e is the atomic molar ratio content of Cr element, 0% < e% ≤ 30%; f is the atomic molar ratio content of Ni element, 0% < f% ≤ 30%; and a + b + c + d + e + f = 100.

[0080] Step 6, preliminary screening:

[0081] Using the valence electron concentration VEC satisfying 6.5 < VEC < 8.38 and the mixing enthalpy satisfying -18 < ΔHmix < -6 as the constraint conditions, screen the candidate set of layer / rod eutectic high-entropy alloys to obtain candidate layer / rod eutectic high-entropy alloys.

[0082] Step 7, final screening:

[0083] Simulate the X-ray diffraction pattern of the candidate layer / rod eutectic high-entropy alloy through Jade software. By analyzing the obtained X-ray diffraction pattern, determine the phase composition of the eutectic two phases; using the melting point difference of the phase composition of the eutectic two phases ≤ 35°C as the constraint condition, screen the candidate layer / rod eutectic high-entropy alloy, and thus obtain the layer / rod eutectic high-entropy alloy.

[0084] The chemical composition expression of the layer / rod eutectic high-entropy alloy finally obtained by the above design method of the present invention is Fe a Al b Ta c Co d Cr e Ni f ; wherein, a is the atomic molar ratio content of the Fe element, 30% ≤ a% ≤ 54%; b is the atomic molar ratio content of the Al element, 3% ≤ b% ≤ 8%; c is the atomic molar ratio content of the Ta element, 5% ≤ c% ≤ 8%; d is the atomic molar ratio content of the Co element, 5% ≤ d% ≤ 15%; e is the atomic molar ratio content of the Cr element, 20% ≤ e% ≤ 30%; f is the atomic molar ratio content of the Ni element, 5% ≤ f% ≤ 30%; and a + b + c + d + e + f = 100.

[0085] Example 1

[0086] This example takes the Fe 50 Al8Ta7Co5Cr 25 Ni5 eutectic high-entropy alloy obtained based on the above design method as an example. Through calculation, it can be known that the valence electron concentration VEC of the Fe 50 Al8Ta7Co5Cr 25 Ni5 eutectic high-entropy alloy in this example is 7.04, and the mixing enthalpy ΔHmix = -8.3636, that is, the valence electron concentration VEC of this example satisfies 6.5 < VEC < 8.38, and the mixing enthalpy ΔHmix satisfies -18 < ΔHmix < -6. And the melting point difference between the two phases calculated by the JMatPro solidification simulation phase diagram is 14 °C.

[0087] The Fe 50 Al8Ta7Co5Cr 25 Ni5 in this example also satisfies 30% ≤ a% ≤ 54%, 3% ≤ b% ≤ 8%, 5% ≤ c% ≤ 8%, 5% ≤ d% ≤ 15%, 20% ≤ e% ≤ 30%, 5% ≤ f% ≤ 30%; and a + b + c + d + e + f = 100.

[0088] This example also provides a preparation method for the above Fe 50 Al8Ta7Co5Cr 25 Ni5 eutectic high-entropy alloy, including the following steps:

[0089] 1) After polishing and cleaning the bulk or granular pure metals of Fe, Al, Ta, Co, Cr, and Ni with a purity of not less than 99.95% by an electronic balance, respectively weigh a total mass of 130 ± 0.5 g of mixed raw materials according to the atomic molar ratio of 50%:8%:7%:5%:25%:5%.

[0090] 2) Place the raw materials in a non-consumable arc melting water-cooled copper crucible in order of melting point from low to high. Then evacuate the furnace until the vacuum degree in the furnace reaches 1×10 -3 After Pa, fill the vacuum non-consumable arc melting furnace with argon gas with a purity of 99.999wt.% as a protective gas for melting. Before melting the raw materials, melt the sponge titanium for two to three minutes. The current is controlled at 600-650A. To ensure uniform composition, the high entropy alloy ingot is turned over at least 5 times. After melting, the molten liquid is turned over into a copper mold to obtain a high entropy alloy plate and a eutectic high entropy alloy sample.

[0091] The present invention is to prepare Fe 50 Al8Ta7Co5Cr 25 The Ni5 eutectic high entropy alloy was tested by scanning electron microscopy, and the test results are as follows Figure 1 shown.

[0092] Figure 1 is the Fe of Example 1 50 Al8Ta7Co5Cr 25 Scanning electron microscope image of Ni5 eutectic high entropy alloy, Figure 1 It can be seen that the Fe prepared in Example 1 50 Al8Ta7Co5Cr 25 The Ni5 eutectic high entropy alloy formed an extremely fine and complete eutectic cell, indicating that the Fe prepared in Example 1 50 Al8Ta7Co5Cr 25 The microstructure of Ni5 eutectic high entropy alloy is composed of layered and rod-shaped eutectic structures.

[0093] The present invention is to prepare Fe 50 Al8Ta7Co5Cr 25 The Ni5 eutectic high entropy alloy was tested by transmission scanning electron microscopy, and the test results are as follows Figure 2 shown.

[0094] Figure 2 is the Fe of Example 1 50 Al8Ta7Co5Cr 25 The bright field image of the transmission scanning electron microscope of the Ni5 eutectic high entropy alloy clearly shows that the Fe 50 Al8Ta7Co5Cr 25 The unit cell of Ni5 eutectic high entropy alloy is composed of regular layers and rod-shaped eutectic structures.

[0095] The present invention is to prepare Fe 50 Al8Ta7Co5Cr 25The Ni5 eutectic high entropy alloy was tested by X-ray diffraction, and the test results are as follows Figure 3 shown.

[0096] Figure 3 is the Fe of Example 1 50 Al8Ta7Co5Cr 25 X-ray diffraction spectrum of Ni5 eutectic high entropy alloy shows that Fe 50 Al8Ta7Co5Cr 25 The phase composition structure of Ni5 eutectic high entropy alloy is composed of BCC structured Fe2AlCr phase and hexagonal close-packed Fe2Ta Laves phase.

[0097] The present invention is to prepare Fe 50 Al8Ta7Co5Cr 25 The temperature rise endothermic curve of Ni5 eutectic high entropy alloy measured by differential scanning calorimetry, and the test results are as follows Figure 4 shown.

[0098] Figure 4 is the Fe of Example 1 50 Al8Ta7Co5Cr 25 The temperature rise endothermic curve of Ni5 eutectic high entropy alloy shows that there is a single and narrow endothermic peak in the figure, which confirms that the Fe 50 Al8Ta7Co5Cr 25 Ni5 eutectic high entropy alloy is indeed a eutectic high entropy alloy and has the eutectic characteristics of regular layer rods.

[0099] The present invention adopts electric spark wire cutting to cut the Fe 50 Al8Ta7Co5Cr 25 A rectangular specimen with a size of 10×10×20 mm was cut out from the Ni5 high entropy alloy plate. The surface of the specimen was polished with 120#, 240#, 400#, 800#, 1000#, 1500#, and 2000# metallographic sandpaper in sequence. The compression performance of Example 1 was tested using a universal testing machine. The test results are shown in FIG. Figure 5 shown.

[0100] Figure 5 is the Fe of Example 1 50 Al8Ta7Co5Cr 25 From the compressive stress-strain curve of Ni5, it can be seen that the Fe 50 Al8Ta7Co5Cr 25 The yield strength of Ni5 is 1669.2MPa, its fracture strength is 1958.4MPa, and its fracture strain is as high as 16.2%, showing good plasticity.

[0101] Example 2

[0102] In this example, the Fe 45 Al8Ta7Co 10 Cr 20 Ni 10 eutectic high-entropy alloy obtained based on the above design method is taken as an example. Through calculation, it can be known that the valence electron concentration VEC of the Fe 45 Al8Ta7Co 10 Cr 20 Ni 10 eutectic high-entropy alloy is 7.29, and the mixing enthalpy ΔHmix = -9.4736, that is, the valence electron concentration VEC of this example satisfies 6.5 < VEC < 8.38, and the mixing enthalpy ΔHmix satisfies -18 < ΔHmix < -6. And the melting point difference between the two phases calculated by the JMatPro solidification simulation phase diagram is 14 °C.

[0103] The Fe 45 Al8Ta7Co 10 Cr 20 Ni 10 in this example also satisfies 30% ≤ a% ≤ 54%, 3% ≤ b% ≤ 8%, 5% ≤ c% ≤ 8%, 5% ≤ d% ≤ 15%, 20% ≤ e% ≤ 30%, 5% ≤ f% ≤ 30%; and a + b + c + d + e + f = 100.

[0104] This example also provides a preparation method for the above-mentioned Fe 45 Al8Ta7Co 10 Cr 20 Ni 10 eutectic high-entropy alloy, including the following steps:

[0105] 1) After polishing and cleaning the bulk or granular pure metals of Fe, Al, Ta, Co, Cr, and Ni with a purity of not less than 99.95% by an electronic balance, weigh the mixed raw materials with a total mass of 130 ± 0.5 g at a molar ratio of 45:8:7:10:20:10 respectively.

[0106] 2) Place the raw materials in a non-consumable arc melting water-cooled copper crucible in ascending order of melting point. Then evacuate to a vacuum degree of 1×10 -3 Pa in the furnace cavity, and then fill the vacuum non-consumable arc melting furnace with argon with a purity of 99.999 wt.% as the protective gas for melting. Before melting the raw materials, first melt the sponge titanium for two to three minutes. Control the current at 600 - 650 A. To ensure the uniformity of the composition, the high-entropy alloy ingot is remelted at least 5 times. After melting, pour the molten liquid into a copper mold to obtain a high-entropy alloy plate, and obtain a eutectic high-entropy alloy sample.

[0107] The present invention conducted a scanning electron microscope test on the Fe 45 Al8Ta7Co 10 Cr 20 Ni 10 eutectic high-entropy alloy prepared by the above preparation method of this example, and the test results are as Figure 6 shown.

[0108] Figure 6 For the Fe 45 Al8Ta7Co 10 Cr 20 Ni 10 eutectic high-entropy alloy of Example 2, as can be seen from Figure 6 the scanning electron microscope image, very fine and complete eutectic cells were formed in the Fe 45 Al8Ta7Co 10 Cr 20 Ni 10 eutectic high-entropy alloy prepared in Example 2, but there were still a small amount of primary phases.

[0109] Comparative Example 1

[0110] Taking the Fe 55 Al8Ta7Co5Cr 20 Ni5 eutectic high-entropy alloy of this comparative example as an example, through calculation, it can be known that the valence electron concentration VEC of the Fe 50 Al8Ta7Co5Cr 25 Ni5 eutectic high-entropy alloy of this example is 7.14, and the mixing enthalpy ΔHmix = -8.3856, that is, the valence electron concentration VEC of this example satisfies 6.5 < VEC < 8.38, and the mixing enthalpy ΔHmix satisfies -18 < ΔHmix < -6. And the melting point difference between the two phases calculated by the JMatPro solidification simulation phase diagram is 20 °C. Although the alloy composition of this comparative example also meets the design requirements, the Fe content does not meet the requirement of 30% ≤ a% ≤ 54% mentioned above.

[0111] And the preparation method of this comparative example is the same as that of Example 1, the difference is only that:

[0112] The eutectic high-entropy alloy of this comparative example is the Fe 55 Al8Ta7Co5Cr 20 Ni5 eutectic high-entropy alloy.

[0113] The present invention conducted a scanning electron microscope test on the Fe 55 Al8Ta7Co5Cr 20 Ni5 eutectic high-entropy alloy prepared by the above preparation method of this comparative example, and the test results are as Figure 7 shown.

[0114] Figure 7 The Fe of Comparative Example 1 55 Al8Ta7Co5Cr 20 Scanning electron microscope image of the Al8Ta7Co5CrNi5 eutectic high-entropy alloy, from Figure 7 It can be seen that large Laves primary phases appeared in the Fe 55 Al8Ta7Co5Cr 20 Al8Ta7Co5CrNi5 eutectic high-entropy alloy, and the alloy composition deviated from the eutectic, forming a hypoeutectic structure. This indicates that when the content of the key alloying elements exceeds

[0115] Example 3

[0116] This example takes the Fe 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 eutectic high-entropy alloy obtained based on the above design method as an example. Through calculation, it can be known that the valence electron concentration VEC of the Fe 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 eutectic high-entropy alloy is VEC = 7.658, and the mixing enthalpy ΔHmix = -11.708, that is, the valence electron concentration VEC of this example satisfies 6.5 < VEC < 8.38, and the mixing enthalpy ΔHmix satisfies -18 < ΔHmix < -6. And the melting point difference between the two phases calculated by the JMatPro solidification simulation phase diagram is 34 °C.

[0117] The Fe of this example 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 satisfies 30% ≤ a% ≤ 54%, 3% ≤ b% ≤ 8%, 5% ≤ c% ≤ 8%, 5% ≤ d% ≤ 15%, 20% ≤ e% ≤ 30%, 5% ≤ f% ≤ 30%; and a + b + c + d + e + f = 100.

[0118] This example also provides a preparation method for the above-mentioned Fe 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 eutectic high-entropy alloy, including the following steps:

[0119] 1) After grinding and cleaning the block or granular pure metals of Fe, Al, Ta, Co, Cr and Ni with a purity of not less than 99.95% by electronic balance, weigh 130±0.5g of mixed raw materials with a total mass of 130±0.5g at a molar ratio of 38.4:3.625:7.4:8:21.75:20.825.

[0120] 2) Place the raw materials in a non-consumable arc melting water-cooled copper crucible in order of melting point from low to high. Then evacuate the furnace until the vacuum degree in the furnace reaches 1×10 -3 After Pa, fill the vacuum non-consumable arc melting furnace with argon gas with a purity of 99.999wt.% as a protective gas for melting. Before melting the raw materials, melt the sponge titanium for two to three minutes. The current is controlled at 600-650A. To ensure uniform composition, the high entropy alloy ingot is turned over at least 5 times. After melting, the molten liquid is turned over into a copper mold to obtain a high entropy alloy plate and a eutectic high entropy alloy sample.

[0121] The present invention is to prepare Fe 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 The eutectic high entropy alloy was tested by scanning electron microscopy, and the test results are as follows Figure 8 shown.

[0122] Figure 8 is Fe of Example 3 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 Scanning electron microscope image of a eutectic high entropy alloy, Figure 8 It can be seen that the Fe prepared in Example 3 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 Extremely fine and complete eutectic cells are formed in the eutectic high entropy alloy, and the unit cell of the high entropy alloy component is composed of regular layered and rod-shaped eutectic structures.

[0123] The present invention is to prepare Fe 38.4 Al 3.625 Ta 7.4 Co8Cr 21.75 Ni 20.825 The eutectic high entropy alloy was tested by X-ray diffraction, and the test results are as follows Fig. 9 shown.

[0124] Fig. 9 is Fe of Example 338.4 Aluminum 3.625 Tantalum 7.4 Cobalt 8 Chromium 21.75 Nickel 20.825 The X-ray diffraction pattern of the eutectic high-entropy alloy shows that Fe 38.4 Aluminum 3.625 Tantalum 7.4 Cobalt 8 Chromium 21.75 Nickel 20.825 The phase composition structure of the eutectic high-entropy alloy consists of an FCC-structured Fe3Ni phase and a close-packed hexagonal Laves phase of the Fe2Ta configuration.

[0125] Example 4

[0126] In this example, taking the Fe 32 Aluminum 3.5 Tantalum 8 Cobalt 8 Chromium 26 Nickel 22.5 eutectic high-entropy alloy as an example, through calculation, it can be known that the valence electron concentration VEC of the Fe 32 Aluminum 3.5 Tantalum 8 Cobalt 8 Chromium 26 Nickel 22.5 eutectic high-entropy alloy is VEC = 7.658, and the mixing enthalpy ΔHmix = -12.618, that is, the valence electron concentration VEC of this example satisfies 6.5 < VEC < 8.38, and the mixing enthalpy ΔHmix satisfies -18 < ΔHmix < -6. And the melting point difference between the two phases calculated by the JMatPro solidification simulation phase diagram is 13 °C.

[0127] The Fe 32 Aluminum 3.5 Tantalum 8 Cobalt 8 Chromium 26 Nickel 22.5 in this example also satisfies 30% ≤ a% ≤ 54%, 3% ≤ b% ≤ 8%, 5% ≤ c% ≤ 8%, 5% ≤ d% ≤ 15%, 20% ≤ e% ≤ 30%, 5% ≤ f% ≤ 30%; and a + b + c + d + e + f = 100.

[0128] This example also provides a preparation method for the above-mentioned Fe 32 Aluminum 3.5 Tantalum 8 Cobalt 8 Chromium 26 Nickel 22.5 eutectic high-entropy alloy, including the following steps:

[0129] 1) After polishing and cleaning the bulk or granular pure metals of Fe, Al, Ta, Co, Cr, and Ni with a purity of not less than 99.95% using an electronic balance, weigh the total mass of 130 ± 0.5 g of the mixed raw materials at a molar ratio of 32:3.5:8:8:26:22.5 by atomic ratio.

[0130] 2) Place the raw materials in a non-consumable arc melting water-cooled copper crucible in ascending order of melting point. Then evacuate to a vacuum degree of 1×10 -3 Pa in the furnace cavity, and then fill the vacuum non-consumable arc melting furnace with argon with a purity of 99.999 wt.% as the protective gas for melting. Before melting the raw materials, first melt the sponge titanium for two to three minutes. Control the current at 600 - 650 A. To ensure uniform composition, the high-entropy alloy ingot is remelted at least 5 times. After melting, pour the molten liquid into a copper mold to obtain a high-entropy alloy plate, and obtain a eutectic high-entropy alloy sample.

[0131] The present invention conducts a scanning electron microscope test on the Fe 32 Al 3.5 Ta8Co8Cr 26 Ni 22.5 eutectic high-entropy alloy prepared by the above preparation method of this embodiment, and the test results are as Fig.10 shown.

[0132] Fig.10 For the Fe 32 Al 3.5 Ta8Co8Cr 26 Ni 22.5 scanning electron microscope image of the eutectic high-entropy alloy in Example 4, it can be seen from Fig.10 that in the Fe 32 Al 3.5 Ta8Co8Cr 26 Ni 22.5 eutectic high-entropy alloy prepared in Example 4, extremely fine and complete eutectic cells are formed, but there are still a small amount of primary phases.

[0133] Comparative Example 2

[0134] This comparative example takes the Fe 36 Al7Ta9Co 10 Cr 19 Ni 19 eutectic high-entropy alloy obtained based on the above design method as an example. Through calculation, it can be known that the valence electron concentration VEC of the Fe 36 Al7Ta9Co 10 Cr 19 Ni 19 eutectic high-entropy alloy in this comparative example is 7.48, and the mixing enthalpy ΔHmix = -12.798, that is, the valence electron concentration VEC of this comparative example satisfies 6.5 < VEC < 8.38, and the mixing enthalpy ΔHmix satisfies -18 < ΔHmix < -6. And the melting point difference between the two phases calculated by the JMatPro solidification simulation phase diagram is 14°C. But it does not satisfy 5% ≤ c% ≤ 8%.

[0135] The preparation method of this comparative example is the same as that of Example 1, except that:

[0136] The eutectic high entropy alloy of this comparative example is Fe 36 Al7Ta9Co 10 Cr 19 Ni 19 Eutectic high entropy alloy.

[0137] The present invention is to prepare Fe 36 Al7Ta9Co 10 Cr 19 Ni 19 The eutectic high entropy alloy was tested by scanning electron microscopy, and the test results are as follows Fig.11 shown.

[0138] Fig.11 Fe of Comparative Example 2 36 Al7Ta9Co 10 Cr 19 Ni 19 Scanning electron microscope image of a eutectic high entropy alloy, Fig.11 It can be seen that the Fe prepared in Comparative Example 2 36 Al7Ta9Co 10 Cr 19 Ni 19 Eutectic high entropy alloys have more Laves primary phases and a small amount of eutectic structure, and the alloy composition deviates from the eutectic point.

[0139] The present invention is to prepare Fe 36 Al7Ta9Co 10 Cr 19 Ni 19 The eutectic high entropy alloy was tested by X-ray diffraction, and the test results are as follows Fig.12 shown.

[0140] Fig.12 Fe of Comparative Example 2 36 Al7Ta9Co 10 Cr 19 Ni 19 From the X-ray diffraction spectrum of the eutectic high entropy alloy, it can be seen that Fe 36 Al7Ta9Co 10 Cr 19 Ni 19 The phase composition structure of the eutectic high entropy alloy is composed of the Fe3Ni phase with FCC structure and the Laves phase with hexagonal Fe2Ta configuration.

[0141] It should be noted that, when performing the above-mentioned scanning electron microscope test and transmission electron microscope test, the present invention first uses electric spark wire cutting to cut a cross-sectional sample with a size of 10×20×4 mm from the high entropy alloy plate, and then polishes the sample surface with 120#, 240#, 400#, 800#, 1000#, 1500#, and 2000# metallographic sandpaper, and then polishes the sample, and then performs scanning electron microscope test and transmission electron microscope test.

[0142] When the present invention performs the above X-ray diffraction test, the scanning angle is 20° to 100° and the scanning speed is 0.02° / s.

[0143] When the differential scanning calorimetry test is performed, the heating rate is 10K / min and the termination temperature is 1450°C.

[0144] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A design method for a layer / rod eutectic high entropy alloy, characterized in that: Including the following steps: Obtain the alloy composition and eutectic microstructure morphology of the eutectic alloy system in the publicly available literature data, and establish a database with the corresponding data of the eutectic microstructure morphology as input data and the alloy composition of the eutectic alloy system as the corresponding output data; Taking the microstructure morphology including lamellar eutectic and / or rod eutectic as a constraint condition, screen the database to obtain a candidate set of eutectic alloy systems with lamellar eutectic and / or rod eutectic; obtain the eutectic point composition of each eutectic alloy system in the candidate set of eutectic alloy systems as the candidate set of basic alloy elements; Obtain the types and contents of alloy elements with eutectic point composition in the candidate set of basic alloy elements, sort the types of alloy elements with eutectic point composition in descending order of content, and take the alloy element type with the largest content as the key alloy element; Taking the types of alloy elements that can be infinitely solid-soluted and / or have a eutectic tendency with the key alloy element as a constraint condition, screen the database to obtain a candidate set of doped alloy elements; Taking several doped alloy elements selected from the candidate set of doped alloy elements as doping sources, partially replace the key alloy element in the candidate set of basic alloy elements, and form a eutectic high-entropy alloy system composed of at least five alloy elements according to the predefined atomic molar ratio content, and establish a candidate set of lamellar / rod eutectic high-entropy alloys; Taking the valence electron concentration VEC satisfying 6.5 < VEC < 8.38 and the mixing enthalpy ΔHmix satisfying -18 < ΔHmix < -6 as constraint conditions, screen the candidate set of lamellar / rod eutectic high-entropy alloys to obtain candidate lamellar / rod eutectic high-entropy alloys; Determine the phase composition of the eutectic two phases of the candidate lamellar / rod eutectic high-entropy alloy, and screen the candidate lamellar / rod eutectic high-entropy alloy with the constraint condition that the melting point difference between the eutectic two phases satisfies ≤ 35 °C, and the lamellar / rod eutectic high-entropy alloy is obtained; 2. The design method according to claim 1, characterized in that: The melting point difference between the eutectic two phases is obtained through the following steps: Calculate the melting point difference corresponding to the phase composition of the eutectic two phases through JMatPro solidification simulation phase diagram; 3. The design method according to claim 1, characterized in that: The phase composition of the eutectic two phases of the candidate lamellar / rod eutectic high-entropy alloy is determined through the following steps: Simulate the X-ray diffraction spectrum of the candidate lamellar / rod eutectic high-entropy alloy through Jade software, and determine the phase composition of the eutectic two phases by analyzing the obtained X-ray diffraction spectrum; 4. The design method according to claim 1, characterized in that: Taking the conditions of having an atomic radius close to that of the key alloy element, the same crystal structure, and only a single-phase region existing below the liquidus in the binary phase diagram formed with the key alloy element as constraint conditions, screen the alloy elements in the database to obtain alloy elements that can be infinitely solid-soluted with the key alloy element; 5. The design method according to claim 1, characterized in that: Taking the condition that the valence electron concentration VEC of the alloy formed with the key alloy element ≥ 8 as a constraint condition, screen the alloy elements in the database to obtain alloy elements that have a eutectic tendency with the key alloy element.

6. The design method according to claim 1, characterized in that: When the eutectic point composition obtained by screening is a ternary eutectic point composition composed of three alloying elements A, B, and C, a eutectic high-entropy alloy system composed of six alloying elements is formed according to the predefined atomic molar ratio content, and the eutectic high-entropy alloy system meets the following requirements: Its chemical composition expression is A a B b C c D d E e F f ; Among them, A is the key alloying element, a is the atomic molar ratio content of element A, and 30% ≤ a% ≤ 54%; b is the atomic molar ratio content of element B, 0% < b% ≤ x, where x is the atomic molar ratio content of element B in the eutectic point composition; c is the atomic molar ratio content of element C, 0% < c% ≤ y + 1, where y is the atomic molar ratio content of element C in the eutectic point composition; D and E are alloying elements that can be infinitely solid-solved with the key alloying element, d is the atomic molar ratio content of element D, 0% < d% ≤ 15%; e is the atomic molar ratio content of element E, 0% < e% ≤ 30%; F is an alloying element that has a eutectic tendency with the key alloying element, f is the atomic molar ratio content of element F, 0% < f% ≤ 30%; And a + b + c + d + e + f = 100.

7. A layer / rod eutectic high entropy alloy designed by the design method according to any one of claims 1 to 6, characterized in that: The ternary eutectic composition composed of three alloy elements A, B and C is used as a matrix, and the layer / rod eutectic high entropy alloy is obtained by introducing doping alloy elements D, E and F, and the chemical composition expression of the layer / rod eutectic high entropy alloy is A a B b C c D d E e F f ; Among them, A is the key alloying element, a is the atomic molar ratio content of element A, and 30% ≤ a% ≤ 54%; b is the atomic molar ratio content of element B, 0% < b% ≤ x, where x is the atomic molar ratio content of element B in the eutectic point composition; c is the atomic molar ratio content of element C, 0% < c% ≤ y + 1, where y is the atomic molar ratio content of element C in the eutectic point composition; D and E are alloying elements that can be infinitely solid-solved with the key alloying element, d is the atomic molar ratio content of element D, 0% < d% ≤ 15%; e is the atomic molar ratio content of element E, 0% < e% ≤ 30%; F is an alloying element that has a eutectic tendency with the key alloying element, f is the atomic molar ratio content of element F, 0% < f% ≤ 30%; And a + b + c + d + e + f = 100.

8. The layer / rod eutectic high entropy alloy according to claim 7, characterized in that: The layer / rod eutectic high-entropy alloy has a two-phase structure composed of a first phase and a second phase; The first phase is a BCC phase or FCC; The second phase is a Laves phase.

9. A method for preparing the layer / rod eutectic high entropy alloy according to claim 7, characterized in that: Including the following steps: Weigh the corresponding masses of the respective preparation raw materials according to the stoichiometric relationship of the chemical composition of the layer / rod eutectic high-entropy alloy described in claim 7, and set aside; Place the weighed respective preparation raw materials in a non-consumable arc melting water-cooled copper crucible in ascending order of melting point; After vacuum treatment, fill with a protective gas, and after deoxidation treatment, perform non-consumable arc melting treatment to obtain a molten liquid; After casting the molten liquid, the layer / rod eutectic high-entropy alloy is obtained.

10. The preparation method according to claim 9, characterized in that: The non-consumable arc melting treatment is performed at least 5 times; and each time during the treatment, the current is controlled at 600 A to 650 A, and the duration is 3 min to 5 min; The protective gas is argon with a purity ≥ 99.999 wt.%; The vacuum treatment is performed to a vacuum degree of ≤1×10 -3 Pa; The deoxidation treatment is carried out by placing titanium sponge and the respective preparation raw materials in a non-consumable arc melting water-cooled copper crucible, and first melting the titanium sponge for 2 min to 3 min to remove the residual oxygen in the furnace.

Citation Information

Patent Citations

  • Eutectic high-entropy alloy component design method and device based on machine learning

    CN113870957A

  • Method for preparing iron-based nanocrystalline alloy based on Python process screening design

    CN114388078A

  • Design method of nano L12 phase precipitation strengthened FCC (fluid catalytic cracking)-based high-entropy alloy

    CN115295100A

  • Method for component design of composite variable high-entropy alloy

    CN116936004A

  • Structural classification and performance prediction method for medium / high-entropy alloy prepared through selective laser melting

    CN117594141A